The mental health of health professionals: A forgotten and overlooked issue - Rodríguez Lazaro, Lester Byron (2024)
Health professionals are subjected daily to stressful and demanding situations, from which they receive a negative effect on their psychological balance. Constant and numerous studies document the high prevalence of psychological alterations. Thus, a Mexican study in 2006 evaluated 173 professionals, doctors and nurses, and found that 43.2% had a high prevalence of depersonalization and at least 41.4% of emotional exhaustion (1). In addition, when the mental health of 178 primary care health workers in Spain was evaluated during 2014, 39.3% were found with burnout syndrome, with the male gender, being an urban employee, and workload prevailing as associated factors.